Pengaruh Video Pembelajaran Aplikasi Pahamify sebagai Media Belajar terhadap Hasil Belajar Siswa Kelas XI IPA pada Mata Pelajaran Sejarah di SMA Negeri 5 Medan - Simbolon, Hannah Felicia; Tanjung, Samsidar (Innovative: Journal Of Social Science Research, 2024)
This research aims to see the influence of the Pahamify application learning videos as a learning medium on the learning outcomes of class XI Science students in History lessons at SMA Negeri 5 Medan. The method used is quantitative analysis with case control using the t test. The samples in these two research groups each amounted to 36 people. From this research, it is known that there was an increase in learning outcome scores in the group taught using the Ruangguru application (control) and in the group taught using the Pahamify application (experiment). The mean post-test score in the control group was 75.22 and in the experimental group was 84.78. The difference between the pre-test and post-test mean scores in the experimental group (29.56) was higher than the control (19.44). Based on the results of the different test (t test), it is proven that the use of the Pahamify application is more influential than the Ruangguru application in improving learning outcomes with a Sig value. (2-tailed) = 0.00 is smaller than 0.05.